Women Finding Their Voices in the Symbolic Order of American Society - Damjanoski, Milan (VERMILION International Journal of Literature and Art, 2019)
The aim of this article is to show the struggle of women from various cultural, ethnic, race and sexual backgrounds to find their voices amid the confines of the Symbolic Order of contemporary American society. Through the medium of language, society imposes and perpetuates the roles which its members have to accept and abide by. Due to the fact that the Symbolic Order and language as its articulation are male-centred, they serve to entrap women in roles which define them in accordance with the dominant logocentric concepts. They are forced into mimicry, having to use an alien voice, while theirs is forced into the background, into the “semiotic”. The autobigraphical works by Maxine Hong Kinston, Audre Lorde and Minnie Bruce Pratt present us with the social, gender, sexual and racial prejudices, struggles and obstacles they had to go through in American society, but also with a powerful set of strategies to find and express their voice and identity in life and literature.
Keywords: American society, Lacan, symbolic order, issues of representation, feminism, women’s writing